Relationship Between Sport Motivation Climate Created by Parents and Internal Sport Motivation in Younger and Older Adolescents - Slavković, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
This research aims to identify the dominant type of sports motivation climate created by the mother or father (perceived by adolescents) and the dominant type of sports motivation, as well as to conclude which dimensions of the motivational climate created by parents, the best predict the internal sport motivation, to apply this knowledge in educational work, contribute to the proper development of young sportsmen and better sports results. We are also interested in whether this relationship differs between respondents in the period of early and middle adolescence. The study was conducted on a sample of 200 adolescents who play sports, aged 11–19. The Sports Motivation Scale – SMS-28 was used to measure external, internal and amotivation, while the Perceived Motivational Climate Questionnaire was used to measure the perceived sport motivation climate (Climate in Sport Questionnaire 2 – PIMCQ-2). The results of the research showed that the motivational climate created by the father and mother in the subsample of younger adolescents predicts 35.7% of the variance in internal sport motivation (p < 0.05), while the same statistical model is not statistically significant in the subsample of older adolescents. The most important factor in predicting internal sports motivation is the learning-oriented motivational climate created by the mother. The results indicate a negative effect of the achievement-oriented motivational climate, which makes adolescents underestimate the beauty of playing sports and improving sports skills, while their focus is on competitive spirit and overcoming opponents, which leads to increased amotivation.